Five cases of cyclical Cushing's syndrome. Issue 6507 (23rd November 1985) - Atkinson, A B; Kennedy, A L; Carson, D J; Hadden, D R; Weaver, J A; Sheridan, B
Abstract : Reported cases of cyclical Cushing's syndrome are rare. Of 14 successive patients with Cushing's syndrome nine collected sequential urine samples for the estimation of cortisol:creatinine ratio. Five had cyclical Cushing's syndrome while two had considerable variation in urinary cortisol excretion without a cyclical pattern being established. Two of the five patients with a cyclical syndrome had paradoxical responses to dexamethasone. In only one patient with a cyclical pattern did the cortisol:creatinine ratio fall after treatment with bromocriptine or cyproheptadine, or both. The high incidence of the cyclical form of Cushing's syndrome has important clinical implications. A high index of suspicion of the syndrome is required in patients with symptoms or signs of Cushing's syndrome but with normal cortisol values, in patients with fluctuating cortisol values, and in patients with anomalous responses to dexamethasone. Because of possible variations in steroidogenesis the results of drug studies in Cushing's syndrome must be interpreted cautiously.